2019
DOI: 10.3847/1538-4365/ab16ee
|View full text |Cite
|
Sign up to set email alerts
|

An Hα Imaging Survey of the Low Surface Brightness Galaxies Selected from the Spring Sky Region of the 40% ALFALFA H i Survey

Abstract: We present a narrow Hα-band imaging survey of 357 low surface brightness galaxies (LSBGs) that are selected from the spring sky region of the 40% Arecibo Legacy Fast Arecibo L-band Feed Array (ALFALFA) HI Survey. All the Hα images are obtained from the 2.16 m telescope, operated by Xinglong Observatory of the National Astronomical Observatories, Chinese Academy of Sciences. We provide the Hα fluxes and derive the global star formation rates (SFRs) of LSBGs after the Galactic extinction, internal extinction, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 76 publications
(130 reference statements)
4
31
0
Order By: Relevance
“…Our previous series study based on the LSBGs selected from ALFALFA sample with optical surface brightness measured from SDSS images (Du et al 2015;He et al 2019;Du et al 2019) have shown that the LSBGs have much lower metallicity (Du et al 2017), follow the Tully-Fisher relation (Du et al 2019), and have similar mass-light ratios to the high surface brightness galaxies (Du et al 2020). The Hα images of our HI selected LSBG sample also shows that the star formation surface density has a very weak correlation with the gas surface density, the star formation surface density is much lower than the prediction of Kennicutt-Schmidt law (Kennicutt 1998;Kennicutt & Evans 2012), leading to a significantly longer gas depletion time scales, and low star formation efficiency (Lei et al 2018(Lei et al , 2019.…”
supporting
confidence: 56%
“…Our previous series study based on the LSBGs selected from ALFALFA sample with optical surface brightness measured from SDSS images (Du et al 2015;He et al 2019;Du et al 2019) have shown that the LSBGs have much lower metallicity (Du et al 2017), follow the Tully-Fisher relation (Du et al 2019), and have similar mass-light ratios to the high surface brightness galaxies (Du et al 2020). The Hα images of our HI selected LSBG sample also shows that the star formation surface density has a very weak correlation with the gas surface density, the star formation surface density is much lower than the prediction of Kennicutt-Schmidt law (Kennicutt 1998;Kennicutt & Evans 2012), leading to a significantly longer gas depletion time scales, and low star formation efficiency (Lei et al 2018(Lei et al , 2019.…”
supporting
confidence: 56%
“…One reason for such high values is the low density of their gaseous disks that prevents an efficient star formation ( [33,183]) capable to turn the primordial HI disc in a stellar one as it occurs in HSB spirals. In fact, in LSB galaxies we find: Σ H I ∼ 5 M pc −2 (see Figures 6and 14, [200,203]) a value that is about half or less that in HSB galaxies of similar stellar mass ( [34]) and, therefore, according to the Kennicutt criteria [218,219], a value which is below the star formation threshold ( [34,199,219,220]) implying that the gas is not ready to collapse and form stars [34,150,[221][222][223]. In fact, the star formation rate (SFR) in LSBs is very low, usually 0.1 M yr −1 , i.e., at least one order of magnitude lower than in HSB spirals ( [200,224], see also Table 3 in [225] and Table 2 in [203]).…”
Section: Structural Properties Of Lsb Galaxies 4659mentioning
confidence: 69%
“…LSBs galaxies are (obviously) characterised by low surface density exponential stellar discs [200][201][202]. Inside their 25 B magnitude isophotal radii, the stellar disk surface densities < Σ > are in the range (10 to 20) M /pc 2 (see Table 2 in [203]), values about 5-10 times smaller than those in HSB spirals of similar stellar disk masses. Noticeably, LSBs cover, in the range of their stellar disk masses M D , the whole range found in spirals, from ∼10 7 M to ∼10 11 M (see Figures 8,11 and 12).…”
Section: Structural Properties Of Lsb Galaxies 4659mentioning
confidence: 99%
See 1 more Smart Citation
“…In our analysis, we consider the 6dFGS sample in the DES Y1 Gold footprint [30] for the dN/dz measurement and the redshift range of the sample is limited to z ≤ 0.15. This range would include redshifts of our LS-BGs because Hα-selected LSBG samples reside within a few hundreds Mpc [19,31]. As described in the DR3 report [29], we only use samples with the redshift-quality flag Q = 3, 4.…”
Section: B Spec-z Samplementioning
confidence: 99%